Ficções e suas incursões entre a vida e a arte: uma produção em arte e tecnologia - Lima, Cíntia Medianeira Bitencourt de (2017)
This research, developed in Visual Poetics, in the Line Art and Technology, focuses on the creation of a persona and its factoids through performance and photoperformance or photographic staging, constituting through insertions of analog and digital resources, which resulted In a hybrid poetic. It seeks to establish relations between the interactors with the work in process and, from the interaction of the interactor in the cyberspace with the persona, proposes to reflect about reality and fiction in the current artistic production. The text relates the artistic practice proposed in the context of digital media and its implications in contemporary art, encompassing issues involving cyberspace. It deals with performance and staging in the course of the conception of the persona, and finally brings the incursions of the research proposal through fiction that travel the edges of life and art in order to contribute to the reflections and questions of the study. As a theoretical support, she dialogues with authors such as Lucia Santaella, Priscila Arantes, Diana Domingues, Arlindo Machado, Steven Johnson, Bruno Latour, Gilbert Simondon, Renato Cohen, Ana Goldenstein Carvalhaes, Annateresa Fabris, François Soulages, Rosalind Krauss, Charlotte Cotton, Fábio Oliveira Nunes, among others. The poetic production resulted in the legitimation of a persona through social networks, affirming its existence through the dissemination and interaction with the interactors. The persona thus comes to life as a fashion designer inserted in the context of contemporary art.